Behave: The biology of humans at our best and worst - Sapolsky, Robert (London Vintage, 2017)
Behave is one of the most dazzling tours d$1 (Bhorizon of the science of human behavior ever attempted. Moving across a range of disciplines, Sapolsky$1 (Ba neuroscientist and primatologist$1 (Buncovers the hidden story of our actions. Undertaking some of our thorniest questions relating to tribalism and xenophobia, hierarchy and competition, and war and peace, Behave is a towering achievement$1 (Ba majestic synthesis of cutting-edge research and a heroic exploration of why we ultimately do the things we do . . . for good and for ill.s
Keywords: Biology of Humans; Non-fiction science